Absence of evidence for Palaeoproterozoic eclogite-facies metamorphism in East Antarctica: no record of subduction orogenesis during Nuna development - Dillon A. Brown (Nature Portfolio, 2021)
Abstract The cratonic elements of proto-Australia, East Antarctica, and Laurentia constitute the nucleus of the Palaeo-Mesoproterozoic supercontinent Nuna, with the eastern margin of the Mawson Continent (South Australia and East Antarctica) positioned adjacent to the western margin of Laurentia. Such reconstructions of Nuna fundamentally rely on palaeomagnetic and geological evidence. In the geological record, eclogite-facies rocks are irrefutable indicators of subduction and collisional orogenesis, yet occurrences of eclogites in the ancient Earth (> 1.5 Ga) are rare. Models for Palaeoproterozoic amalgamation between Australia, East Antarctica, and Laurentia are based in part on an interpretation that eclogite-facies metamorphism and, therefore, collisional orogenesis, occurred in the Nimrod Complex of the central Transantarctic Mountains at c. 1.7 Ga. However, new zircon petrochronological data from relict eclogite preserved in the Nimrod Complex indicate that high-pressure metamorphism did not occur in the Palaeoproterozoic, but instead occurred during early Palaeozoic Ross orogenesis along the active convergent margin of East Gondwana. Relict c. 1.7 Ga zircons from the eclogites have trace-element characteristics reflecting the original igneous precursor, thereby casting doubt on evidence for a Palaeoproterozoic convergent plate boundary along the current eastern margin of the Mawson Continent. Therefore, rather than a Palaeoproterozoic (c. 1.7 Ga) history involving subduction-related continental collision, a pattern of crustal shortening, magmatism, and high thermal gradient metamorphism connected cratons in Australia, East Antarctica, and western Laurentia at that time, leading eventually to amalgamation of Nuna at c. 1.6 Ga.